2017
DOI: 10.1021/acschembio.7b00007
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of the Competence Stimulating Peptides (CSPs) in Streptococcus pneumoniae Reveal Motifs Critical for Intra-group and Cross-group ComD Receptor Activation

Abstract: Streptococcus pneumoniae is a highly recombinogenic human pathogen that utilizes the competence stimulating peptide (CSP)-based quorum sensing (QS) circuitry to acquire antibiotic resistance genes from the environment and initiate its attack on the human host. Modulation of QS in this bacterium, either inhibition or activation, can therefore be used to attenuate S. pneumoniae infectivity and slow down pneumococcal resistance development. In this study we set to determine the molecular mechanism that drives CSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
151
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 47 publications
(161 citation statements)
references
References 44 publications
8
151
2
Order By: Relevance
“…In a previous work, Yang et al. identified a truncated CSP2 sequence that can effectively activate the ComD2 receptor, CSP2‐desK16‐K17 (termed here CSP2(15)) . Thus, in this work, we used this truncated scaffold as the starting point for the development of pan‐group modulators.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous work, Yang et al. identified a truncated CSP2 sequence that can effectively activate the ComD2 receptor, CSP2‐desK16‐K17 (termed here CSP2(15)) . Thus, in this work, we used this truncated scaffold as the starting point for the development of pan‐group modulators.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al. have shown that replacing Asp10 in CSP2 with its d enantiomer increases the potency of the peptide by ≈20‐fold, and that a doubly mutated analogue, CSP2‐E1Ad10, is a potent ComD2 inhibitor . We therefore evaluated whether these mutations lead to the same enhancement of potency in CSP2(15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations